Effectiveness of a Layer-by-Layer Microbubbles-Based Delivery System for Applying Minoxidil to Enhance Hair Growth - Liao, Ai-Ho (Theranostics, 2016)
Minoxidil (Mx) is a conventional drug for treating androgenetic alopecia, preventing hair loss, and promoting hair growth. The solubility of Mx has been improved using chemical enhancement methods to increase its skin permeability over the long term. This study created a new ultrasound (US) contrast agent—albumin-shelled microbubbles (MBs) that absorb chitosan oligosaccharide lactate (COL) and Mx—and combined it with sonication by US energy in the water phase to enhance hair growth while shortening the treatment period. COL and Mx grafted with MBs (mean diameter of 1480 nm) were synthesized into self-assembled complexes of COL-MBs and Mx-COL-MBs that had mean diameters of 4150 and 4500 nm, respectively. The US was applied at 3 W/cm(2) for 1 min, and combined with Mx-COL-MBs containing 0.3% Mx. The diffusion of Mx through the dialysis membrane from Mx-COL-MB during US (US+Mx-COL-MB) was more rapid at pH 4 than at pH 7.4, which is favorable given that the environment of the scalp is mildly acidic (pH=4.5-5.5). In Franz diffusion experiments performed in vitro, the release rates at 18 hours in the US+Mx-COL-MBs and US+MBs+Mx groups resulted in 2.3 and 1.7 times the penetration and deposition, respectively, of Mx relative to the group with Mx alone. During 21 days treatment in animal experiments, the growth rates at days 10 and 14 in the US+Mx-COL-MBs group increased by 22.6% and 64.7%, respectively, and there were clear significant differences (p<0.05) between the US+Mx-COL-MBs group and the other four groups. The use of US+Mx-COL-MB in the water phase can increased the effects of Mx so as to shorten the telogen phase, and also increase both the diameter of keratinized hair shafts and the size of hair follicles without causing skin damage.